(untitled) (Swiss Medical Weekly, 2021)
The rate of emergency operations for incarcerated and strangulated ventral hernias is about 10–15%, with worse outcomes than elective surgery. A recent laparoscopic technique called the enhanced-view totally extraperitoneal approach (eTEP) was shown to be indicated in elective repair of ventral and incisional hernias, and has a lower rate of postoperative morbidity than the Rives-Stoppa technique, while having the same indications. However, use of the eTEP laparoscopic technique in emergency ventral hernia repair has not yet been reported. We report the case of a 57-year-old white male, with history of multiple abdominal interventions by laparotomy, admitted to the emergency department with progressive vomiting and periumbilical pain for 3 days. On clinical examination, we found a strangulated incisional para-umbilical hernia with local cellulitis and tenderness in the right flank. Abdominal computed tomography confirmed the diagnosis and showed some signs of thickening of the intestinal wall and multiple ventral hernias. The patient was admitted and operated on the same day with use of the eTEP technique and without the need for intestinal resection. The patient was discharged on postoperative day 5. The main complication was the presence of a seroma diagnosed and drained by means of an extraperitoneal laparoscopy after 3 weeks. Total resolution of the seroma was confirmed at 1-year follow up. Incarcerated and strangulated ventral hernias are still classically treated by laparotomy. This case report shows for the first time that the eTEP procedure can be applied for abdominal wall surgery also in the emergency setting in selected patients. We hypothesise that this new procedure can be a promising approach leading fewer postoperative complications and shorter hospital stays.